Developing Product Sustainability Using Life Cycle Analysis: Case Study Electric Cooker Product - ATSANI, Sarah Iftin; WENJIA, Liu (International Journal of Environmental, Sustainability, and Social Science, 2024)
Recently, the concept of sustainable development has emerged as a solution to environmental problems. It is widely recognized that the choices individuals make in their daily purchases and consumption patterns have a significant impact on the environment. As such, it is incumbent upon everyone to adopt sustainable lifestyles and strive to preserve resources for future generations. One area where this can be achieved is through product development. Despite the importance of sustainable products, their availability remains limited. In this study, the analysis was performed on a popular electric cooker as a sample product. Various aspects of the product were examined, including the life cycle, the raw materials used, the processing stage, usage phase, and end-of-life. The goal of this study is to gain valuable insights and propose improvements for a more sustainable version of the product. The environmental impact of each stage of the product’s life cycle was also analysed. By this method, some practical approaches for specific steps can be proposed to make the product more sustainable and reduce the harmful impact on the environment. Overall, it is found that there were many opportunities to adjust the various stages of the product’s life cycle to make it more sustainable.